2022
DOI: 10.33963/kp.a2022.0080
|View full text |Cite
|
Sign up to set email alerts
|

Safety and feasibility of simultaneous left and right heart catheterization via single-arm arterial and venous access

Abstract: Background: Catheterization via the radial artery has become the method of choice for evaluation of the coronary arteries; however in patients requiring simultaneous coronary and right heart catheterization upper extremity access is not commonly used. Aims:In the present study we aimed to assess whether simultaneous left and right heart catheterization via the radial artery and antecubital vein might increase the vascular access site complications. Methods:In this prospective cohort study, 49 patients with con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…While entry can use any vein down to the wrist, the 110-cm commercial catheters presently available are usually not long enough for many patients; the antecubital region is most commonly used. As mentioned by Saedi et al [9], the medial vein is preferred, but even lateral veins can be successful as long as the 90-degree cephalic-axillary junction is respected. Venous catheterization is a painless procedure and certainly less of a hazard than central neck veins or femoral veins.…”
Section: Il N'y a De Nouveau Que Ce Qui Est Oublié [There Is Nothing ...mentioning
confidence: 97%
See 1 more Smart Citation
“…While entry can use any vein down to the wrist, the 110-cm commercial catheters presently available are usually not long enough for many patients; the antecubital region is most commonly used. As mentioned by Saedi et al [9], the medial vein is preferred, but even lateral veins can be successful as long as the 90-degree cephalic-axillary junction is respected. Venous catheterization is a painless procedure and certainly less of a hazard than central neck veins or femoral veins.…”
Section: Il N'y a De Nouveau Que Ce Qui Est Oublié [There Is Nothing ...mentioning
confidence: 97%
“…Saedi et al [9], in this issue of the Journal, have demonstrated their success with using the forearm as the venous and arterial catheterization location. They presented a series of patients with a congenital or valvular disease requiring arterial/venous catheterization and compared it against a historical control of arterial access only.…”
Section: Il N'y a De Nouveau Que Ce Qui Est Oublié [There Is Nothing ...mentioning
confidence: 99%